The Effect of Arm Muscle Training on Smash Ability in Badminton Athletes at PB. New Binatama - Santoso, Agung Budi; Sin, Tjung Hauw; Edmizal, Eval; Purnomo, Eko (STKIP Pasundan, 2025)
This study aims to determine the effect of arm muscle training on the smash ability of badminton athletes at PB. New Binatama. This research used a quantitative approach with a one-group pretest-posttest experimental design. The sample consisted of six athletes selected through purposive sampling. Data were collected using smash ability tests conducted before and after four weeks of arm muscle training. The data analysis technique employed was the paired sample t-test and N-Gain analysis. The results showed a significant difference between the pre-test and post-test scores with a t-value of –12.011 and a significance level of 0.000 (p < 0.001). The average N-Gain score was 0.16 (15.7%), which falls into the low category. These findings indicate that arm muscle training significantly improves smash ability in badminton athletes, although the overall effectiveness remains limited. Longer training duration is recommended to achieve optimal results.